2021
DOI: 10.1021/jasms.1c00068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryoablation Treatment on the Protein Expression Profile of Low-Grade Central Chondrosarcoma Identified by LC-ESI-MS/MS

Abstract: The use of cryoablation/cryosurgery in treating solid tumors has been proven as a unique technique that uses lethal temperatures to destroy the tumors and impart better functions for the affected organs. This novel technique recently demonstrated the best clinical results in chondrosarcoma (CSA) with faster recovery, less recurrence, and metastasis. Due to the resistant nature of CSA to chemo and radiation therapy, cryoablation comes to light as the best alternative approach. Therefore, for the first time, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…In addition, a recent study by Xu et al demonstrated that rabbit pedicle freezing autografts showed higher survival rates when expressing several bone revitalization proteins [14]. Recently, we used proteomics to explore and study the freezing and irradiation treated autografts of osteosarcoma, chondrosarcoma, and giant cell tumor in greater detail [15,16]. Our previous proteomic investigations uncovered several proteins whose expressions were positively altered and may be able to restore and remodel bone defects through regulating several pathways.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a recent study by Xu et al demonstrated that rabbit pedicle freezing autografts showed higher survival rates when expressing several bone revitalization proteins [14]. Recently, we used proteomics to explore and study the freezing and irradiation treated autografts of osteosarcoma, chondrosarcoma, and giant cell tumor in greater detail [15,16]. Our previous proteomic investigations uncovered several proteins whose expressions were positively altered and may be able to restore and remodel bone defects through regulating several pathways.…”
Section: Introductionmentioning
confidence: 98%